BIOLOGY OF COCCINELLA TRANSVERSALIS (FABRICIUS) ON DIFFERENT APHID SPECIES - SHUKLA, ABHISHEK; S. JADHAV, DARSHANA (The Bioscan, 2013)
The average biology of C. transversalis were showed that when it was reared on A. craccivora the egg, total larval, pupal and adult male and female periods was 2.70 ± 0.76, 12.90 ± 1.44, 2.62 ± 0.63, 31.58 ± 3.22 and 39.10 ± 3.37 days, respectively, whereas on L. erysimi these periods were 2.70 ± 0.76, 12.68 ± 1.63, 2.62 ± 0.69 and 30.12 ± 4.49 and 33.88 ± 2.56 days, respectively, while on M. persicae these periods were 2.70 ± 0.76, 12.98 ± 1.93, 2.52 ± 0.61 and 29.08 ± 4.25 and 37.12 ± 2.27 days, respectively. The mean fecundity of C. transversalis on A. craccivora, L. erysimi and M. persicae were 376.46 ± 47.32, 364.88 ± 27.44 and 377.36 ± 28.96 eggs per female, respectively. Total life cycle of male and female C. transversalis on A. craccivora, L. erysimi and M. persicae were 50.80 ± 3.92, 49.12 ± 4.87 and 48.28 ± 5.38 days and 58.32 ± 3.92, 52.88 ± 3.48 and 56.32 ± 3.07 days, respectively. The average length and width of adult female was 5.37 ± 0.598 mm and 4.26 ± 0.498 mm, respectively, whereas male length and width was 4.85 ± 0.446 mm and 3.82 ± 0.414 mm, respectively.